Multidisciplinary nursing practice in a low-resource setting in Southeast Brazil - Bruno Henrique Souza Izidório; Kátia Eliane Santos Avelar; Flávia dos Santos Lugão de Souza; Patricia Maria Dusek; Agnaldo José Lopes (PAGEPress Publications, 2024)
The various specializations available to nurses represent an investment geared toward providing more qualified patient care. However, little is known about the attitudes of specialized nurses toward multidisciplinarity. The purpose of this study was to investigate nurses' perceptions of multidisciplinarity in the field of specialist nurses, as well as to determine how specialization is associated with improved patient care and nurses' age in a low-resource setting in Southeast Brazil. This cross-sectional study included 70 nurses aged ≥18 years with at least one nursing specialty working at the Regional Health Superintendence of Manhuaçu, Minas Gerais, Brazil. The study participants responded to questions about specialization and its importance in the field of health care. The majority of nurse specialists (84.3%) were between the ages of 20 and 40, and 31.4 percent worked in family health. Eighty percent of nurse specialists agreed that nursing specialization was important. More than 75% agreed that specialization promotes higher quality care and that multidisciplinarity is critical for improving patient care. Seventy percent of participants distrusted online health information. There is a relationship between the importance of having a specialty and better patient care (τb=0.293, p=0.002), and between being a specialist nurse and age (τb=-0.272, p=0.004). Nurses have embraced the concept of multidisciplinarity as a way to improve healthcare. However, they were concerned about the qualifications for nursing specialties.